2020
DOI: 10.3389/fonc.2020.00457
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multimodal Radiomics Model for Preoperative Prediction of Lymphovascular Invasion in Rectal Cancer

Abstract: Objective: To explore a new predictive model of lymphatic vascular infiltration (LVI) in rectal cancer based on magnetic resonance (MR) and computed tomography (CT). Methods: A retrospective study was conducted on 94 patients with histologically confirmed rectal cancer, they were randomly divided into training cohort (n = 65) and validation cohort (n = 29). All patients underwent MR and CT examination within 2 weeks before treatment. On each slice of the tumor, we delineated the volume of interest on T2-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 37 publications
(49 reference statements)
2
60
1
Order By: Relevance
“…However, for esophageal cancer, plain and venous phase CECT scans were not the routine sequences, while a single arterial phase is more in line with clinical practice. Zhang et al (29) established multimodal imaging radiomics model using MRI (T2WI, DWI) and venous phase CECT images to predict LVI status in rectal cancer, yielding the best performance compared with every single model. This implies that incorporating MRI or PET/CT images into our model to develop a multimodal radiomics model may improve the predictive performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for esophageal cancer, plain and venous phase CECT scans were not the routine sequences, while a single arterial phase is more in line with clinical practice. Zhang et al (29) established multimodal imaging radiomics model using MRI (T2WI, DWI) and venous phase CECT images to predict LVI status in rectal cancer, yielding the best performance compared with every single model. This implies that incorporating MRI or PET/CT images into our model to develop a multimodal radiomics model may improve the predictive performance.…”
Section: Discussionmentioning
confidence: 99%
“…The model established by radiomics features combined with clinical features has high diagnostic efficiency. Zhang et al (29) revealed that multimodal radionics models based on MRI and CECT could be a useful tool for predicting LVI in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Following the present results, there was no statistical difference in the discrimination ability between the T2WI score and CT score (Supplementary Information 1: Table S2 and Table S3 ). Our research displayed a particular application of multi-modality radiomics in the interpretation of rectal cancer and gives a hypothesis that every modality radiomics feature provides different and independent information 28 , 38 . The concise score showed the best discrimination and calibration performance among the multi-modality radiomics scores that included T2WI score and CT score which were independent risk variables in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 83%
“…Radiomics shows multiple advantages in evaluating therapeutic response over traditional imaging analysis [7][8][9][10], thereby providing important details of tissue features [11][12][13][14][15][16][17][18][19]. Mounting evidence indicates potential benefits for radiomics in assessing therapeutic response in LARC [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%